Shape control of composite plates with piezoelectric actuators - Syed Mohamed Ali, Jaffar; Mahmood, Munir Mohamed; Shaik Dawood, Mohd. Sultan Ibrahim (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
In this paper, shape control of composite plates using piezoelectric actuators is being investigated. The goal of this study was to see how composite plates behave when they are integrated with piezoelectric actuators. Modelling and simulation were done using COMSOL Multiphysics software and results were validated using previously published studies. Parametric investigations were carried out to inves-tigate the effect of patch locations and stacking sequences with respect to suppression of deflection. The obtained results showed that for uniformly distributed load considered in this work the patches worked effectively when they were placed at the center of the composite plate.